Simultaneous Estimation of Adjusted Rate of Two Factors using Method of Direct Standardization (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: standardization; adjusted specific; unadjusted crude rate; adjusted crude rate; ratios